2016
DOI: 10.18785/jetde.0901.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Online and Onsite Students’ Learning Outcomes and Experiences in a Massively Open Online Course in China

Abstract: This paper compares the achievements and learning experiences of onsite and online students participating in a Massively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…A literature review on the development of distance higher education, including MOOCs, in China found that by the end of 2018, approximately 201 million Chinese people, 24.3% of those who used the Internet, had received online education, an increase from the end of 2017 amounted to 29.7%. Of those who completed online education, 96.5% used their mobile phones, an increase of 19.9% over the end of 2017 [44,45]. The value of the present research is that the analysis of students' knowledge about MOOC has shown that the Russian DL market requires further modernization and an expanded campaign to inform potential students.…”
Section: Discussionmentioning
confidence: 81%
“…A literature review on the development of distance higher education, including MOOCs, in China found that by the end of 2018, approximately 201 million Chinese people, 24.3% of those who used the Internet, had received online education, an increase from the end of 2017 amounted to 29.7%. Of those who completed online education, 96.5% used their mobile phones, an increase of 19.9% over the end of 2017 [44,45]. The value of the present research is that the analysis of students' knowledge about MOOC has shown that the Russian DL market requires further modernization and an expanded campaign to inform potential students.…”
Section: Discussionmentioning
confidence: 81%
“…There are also numerous studies that have found no meaningful difference between onsite and online learning in terms of student success [101]. Chen and Jia [23] in their study found that there was no significant difference between onsite and online learning in terms of average assignment scores, learning experiences, quality and usability of technology, design of learning assessment, and instructional content. In another study, no significant difference was found on student performance between onsite and online learners in terms of gender and class rank [71].…”
Section: Onsite Learning and Online Learningmentioning
confidence: 95%
“…In the academic year of 2020, the fully online teaching method was implemented for the first time in medicinal chemistry courses at the Faculty of Pharmacy, Silpakorn University. Even though there were previous reports that showed that students in online and face-to-face courses did not differ in their performance, there were some reports on the differences in student performance in terms of grades between learning modes. , The question of the effectiveness of online teaching in medicinal chemistry courses was still in doubt, especially regarding whether the online students could achieve similar learning outcomes and performances as compared to on-site.…”
Section: Student’s Perspectives and Achievements Toward Online Teachingmentioning
confidence: 99%